FEATURES OF DEVELOPMENT OF SCHOOL PEDAGOGICS HEALTH IN TRANSNISTRIA - Valentina V. Abramova; Vladimir N. Irkhin (Obrazovanie i Nauka)
The aim of the investigation is to show the features and to define the directions of development of school pedagogics of health in Pridnestrovian Moldavian Republic (PMR). Methods. The methods involve theoretical analysis of sources in the field of pedagogics of health, statistical data, methods of analogy, comparison, correlation, synthesis of information, studying of the best practices of schools of health of PMR. The principles of system and valeological approaches have been involved as the leading methodological reference points. Results and scientific novelty. Intrinsic characteristics and specifics of school pedagogics of health in PMR are disclosed; its genesis during the PostSoviet period is completely presented; the prospects are defined. Positive experience of preservation, strengthening and formation of health of pupils of Pridnestrovian schools is revealed and analysed. Practical significance of research consists that the received results have predictive character and are suitable for design of the organization of a school education system.